The Valuation and Analysis of Adjustable Rate Mortgages - Kau, James B.; Keenan, Donald C.; Muller, Walter J.; Epperson, James F. (Management Science, 1990)
Securities whose payoffs depend upon the actual path of the underlying state variables pose problems for standard backward-valuation techniques. In this paper, we show that there is a method of solving such problems that requires the addition of but a single auxiliary state variable. The technique is illustrated by examining an adjustable rate mortgage (ARM) with yearly and lifetime caps. The ARM amortizes and can be prepaid at any time. We also handle other prominent features of ARMs including points and teasers. This method of using a single auxiliary state variable to handle path dependencies is a general one, applicable to more complex models of the economic environment and to other financial contracts.